Somatosensory Stimulation With XNKQ Acupuncture Modulates Functional Connectivity of Motor Areas - Nierhaus, Till; Chang, Yinghui; Liu, Bin; Shi, Xuemin; Yi, Ming; Witt, Claudia M.; Pach, Daniel (Frontiers in Neuroscience, 2019)
Xingnao Kaiqiao (XNKQ) acupuncture is an acupuncture technique used for stroke patients. In 24 healthy volunteers, we applied this complex acupuncture intervention, which consists of a manual needle-stimulation on five acupuncture points (DU26 unilaterally, PC6 and SP6 bilaterally). XNKQ was compared to three control conditions: 1.) insertion of needles on the XNKQ acupuncture points without stimulation, 2.) manual needle-stimulation on five nearby non-acupuncture points, and 3.) insertion of needles on the non-acupuncture points without stimulation. In a within-subject design, we investigated functional connectivity changes in resting-state functional magnetic resonance imaging (fMRI) by means of the data-driven eigenvector centrality (EC) approach. With a 2x2 factorial within-subjects design with the two factors stimulation (stimulation vs. non-stimulation) and location (acupuncture points vs. non-acupuncture points) we found decreased EC in precuneus after needle-stimulation (stimulation<non-stimulation), whereas the factor location showed no statistically significant EC differences. XNKQ acupuncture compared with needle-stimulation on non-acupuncture points showed decreased EC primarily in subcortical structures such as caudate nucleus, subthalamic nucleus, and red nucleus. Post-hoc seed-based analysis revealed that the decrease in EC was mainly driven by reduced temporal correlation to primary sensori-motor cortices. The comparison of XNKQ acupuncture with the other two (non-stimulation) interventions showed no significant differences in EC. Our findings support the importance of the stimulation component of the acupuncture intervention and hint toward the modulation of functional connectivity by XNKQ acupuncture, especially in areas involved in motor function. In a next step, similar mechanisms should be validated in stroke patients suffering from motor deficits. ClinicalTrials.gov ID: NCT02453906